2020
DOI: 10.1186/s12889-020-08615-7
|View full text |Cite
|
Sign up to set email alerts
|

A partial mediation effect of father-child attachment and self-esteem between parental marital conflict and subsequent features of internet gaming disorder in children: a 12-month follow-up study

Abstract: Background: This study evaluated whether parent-child attachment and self-esteem may mediate the relationship between parental marital conflict and increases in features of internet gaming disorder (IGD) in children at 1 year. Methods: The baseline and one-year follow-up data for 268 pre-teens aged between 9 and 10 from the Internet User Cohort for Unbiased Recognition of Gaming Disorder in Early Adolescence (iCURE) study were collected. The students were children at low risk for IGD in the initial self-report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Previous studies have also shown that conflict between children and their parents leads to higher levels of IGD after 1 year [ 26 ]. Similarly, disordered gaming symptoms have been found to be higher among adolescents presenting with lower commitment to family social activities, whereas important prevention strategies may focus on strong parent-child relationships [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also shown that conflict between children and their parents leads to higher levels of IGD after 1 year [ 26 ]. Similarly, disordered gaming symptoms have been found to be higher among adolescents presenting with lower commitment to family social activities, whereas important prevention strategies may focus on strong parent-child relationships [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, disordered gaming symptoms have been found to be higher among adolescents presenting with lower commitment to family social activities, whereas important prevention strategies may focus on strong parent-child relationships [ 19 ]. A study among Korean adolescents [ 45 ] revealed that while father-child communication reduced risk of IGD, mother-child relationship did not, which may imply that fathers should make additional efforts in order to improve open and positive communication skills with their children [ 26 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we did not nd important differences in parent-child relationship between 'high-risk' and 'low risk' participants apart from the fact that 'low risk' participants reported better understanding in the context of their parental relationships than 'high risk' participants. Previous studies have shown that con ict between parents resulted in higher IGD features in children after 1 year [35]. Similarly, disordered gaming symptoms were higher with adolescents with lower commitment in family social activities, whereas important prevention represents strong parent-child relationships.…”
Section: Discussionmentioning
confidence: 84%
“…[23]. A study among Korean adolescents [36] revealed that while father-child communication reduced risk of IGD, mother-child relationship did not, which may imply that fathers should make an effort to improve open and positive communication skills with their children [35,36].…”
Section: Discussionmentioning
confidence: 99%